Software architecture fundamentals taking a deeper dive - Richards, Mark.; Ford, Neal.; Safari eBooks ([Sebastopol, Calif.?] : O'Reilly, 2014)
"'Software Architect' places in the top ten of most annual surveys of best jobs, yet no clear path exists from Developer to Architect. Why aren't there more books and training materials to fill this demand? This video series by Neal Ford and Mark Richards starts filling the information gap."--Resource description page.
Title from title screen.
Date of publication from resource description page (viewed Apr. 28, 2014).
Presenters, Neal Ford, Mark Richards.
Keywords: Software architecture; Electronic books